PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA MAJAPAHIT TOUR AND TRAVEL MOJOKERTO - Nanang Andhiyan Mergining Mei; Anna Kridaningsih; Wahyu Adhafiya; Berlina Putri Rifai (Bajang Institute, 2024)
The high number of domestic (domestic) tourists increases competition between travel entrepreneurs in providing satisfaction to consumers. Satisfied consumers will recommend to others. This is what is called loyalty. Between service quality, customer satisfaction and loyalty are a series. From this explanation, this research was carried out which aims to test and prove the influence of service quality on consumer loyalty through consumer satisfaction at Majapahit Tour & Travel Mojokerto.There are 3 variables, namely service quality variables, consumer satisfaction and consumer loyalty. Data processing uses SmartPLS 4.1. The results of the hypothesis test showed that there is an influence of service quality on consumer satisfaction (P values 0.000 < 0.05), there is an influence of service quality on consumer loyalty (P values 0.001 < 0.05), there is an influence of consumer satisfaction on consumer loyalty (P values 0.015 < 0.05) , and a significant influence of service quality on consumer loyalty through consumer satisfaction (P value 0.011 < 0.05). From the adjusted R square value, it is known that the influence of service quality on consumer satisfaction is 68.3%, the influence of service quality and satisfaction on consumer loyalty is 79.5%.